Analysis of strength and thermal conductivity characteristics of layered beams consisting of solid wood and thermal insulation material - M. S. Panova; N. A. Tatus (Vestnik MGSU)
Introduction. The paper describes experimental and theoretical work on the study of the characteristics of a layered building material — thermal timber, consisting of solid wood and layers of thermal insulation. Such materials are used for construction of lightly built wooden houses of private sector and low-rise houses. The peculiarities of this type of materials is that simultaneously with the construction material — wood beam contains a layer or layers of insulation, which allows to reduce the stage of insulation of the house during its construction. Strong wood and absolutely nothing capable of carrying insulation together can give a material whose characteristics are fundamentally different from both the first and the second.Materials and methods. The influence of the number and thickness of layers of thermal insulation and wood on the strength and thermal insulation characteristics of the resulting timber is considered. Knowing the regularities of changing characteristics from the number of layers, it becomes possible to choose a rational system of alternation of wood and insulation layers. Experimental studies of beams with different number and thickness of thermal insulation and power layers were carried out, the total thickness of both power and thermal insulation layers in each beam were the same, but the sequence of laying was changed.Results. The results of the experimental study of the bending strength of the thermal timber and the calculated study of its thermal insulation characteristics are shown. Dependences of maximum loads for beams with different number of wood/insulation layers were experimentally obtained.Conclusions. As a result of the experiments it turned out that the linear bending theory cannot accurately describe the behaviour of the layered material — the withstand load grew with the increase in the number of layers.